2014
DOI: 10.1063/1.4862788
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the vortex migration caused by traveling magnetic wave

Abstract: We studied the magnetisation of a 2 in. diameter YBCO thin film in the presence of traveling magnetic waves with six hall sensors. Simulation based on finite element method was conducted to reproduce the process of magnetisation. We discovered that the magnetisation of YBCO thin film based on traveling waves does not follow the constant current density assumption as used in the standing wave condition. We have shown that the traveling wave is more efficient in transporting the flux into the YBCO thin film, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…High-T c superconducting (HTS) dynamos [1][2][3][4][5][6][7][8][9][10][11][12][13] and other similar HTS "flux pumps" [14][15][16][17][18][19][20][21][22] have been receiving continuing attention recently, as they offer a potential solution to the dc current-injection problem in a wide range of superconducting machines [23] and magnets [24,25]. Specifically, the HTS dynamo is of interest for its predicted output produced by a HTS dynamo arises naturally from Maxwell's laws [12] when applied to a situation in which eddy currents flow in a thin sheet exhibiting a highly nonlinear local resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…High-T c superconducting (HTS) dynamos [1][2][3][4][5][6][7][8][9][10][11][12][13] and other similar HTS "flux pumps" [14][15][16][17][18][19][20][21][22] have been receiving continuing attention recently, as they offer a potential solution to the dc current-injection problem in a wide range of superconducting machines [23] and magnets [24,25]. Specifically, the HTS dynamo is of interest for its predicted output produced by a HTS dynamo arises naturally from Maxwell's laws [12] when applied to a situation in which eddy currents flow in a thin sheet exhibiting a highly nonlinear local resistivity.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical model has shown that, the ac travelling magnetic waves have caused the superconducting current densities with "intermediate values," which were smaller than its critical value. 1 In this paper, we have built an updated CTMFP device, shortening the produced wavelengths to half and quarter of the previous experiment. 10 An updated numerical model have also been built to reveal the causation of the induced intermediate values of current densities.…”
mentioning
confidence: 99%
“…The detailed experimental setup can be found elsewhere. 1,10 In the updated CTMFP magnets, the width of the teeth and slots of each phase winding is 1.25 mm, which is one quarter of the original CTMFP magnets. 10 In this work, we defined a parameter d to describe the relative size of the YBCO sample to the wavelength…”
mentioning
confidence: 99%
See 2 more Smart Citations